2022
DOI: 10.1038/s41591-022-01754-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based tumor mutational burden as a biomarker for atezolizumab in non-small cell lung cancer: the phase 2 B-F1RST trial

Abstract: Tumor mutational burden (TMB) in circulating tumor DNA (ctDNA) has shown promise in predicting benefit from PD-L1/PD-1 inhibitors in retrospective studies. Aiming to assess blood TMB (bTMB) prospectively, we conducted B-F1RST (NCT02848651), an open-label, phase 2 trial that evaluated bTMB as a predictive biomarker for first-line atezolizumab monotherapy in locally advanced or metastatic stage IIIB–IVB non-small cell lung cancer (n = 152). The co-primary endpoints were investigator-assessed objective response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 28 publications
1
81
0
Order By: Relevance
“…Recent research, however, has found that VAF is related to tumor burden and corresponds with prognosis. Patients with reduced VAF, for example, reacted better to atezolizumab in the B-F1RST research ( 23 ). Furthermore, at very low VAF, some discordance between tissue and plasma NGS may be identified ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research, however, has found that VAF is related to tumor burden and corresponds with prognosis. Patients with reduced VAF, for example, reacted better to atezolizumab in the B-F1RST research ( 23 ). Furthermore, at very low VAF, some discordance between tissue and plasma NGS may be identified ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the FDA approved the FoundationOneCDX assay (Foundation Medicine, Inc, Cambridge, MA, USA), a next generation sequencing test, as a companion diagnostic for pembrolizumab treatment in unresectable or metastatic TMB-high (TMB ≥ 10 mutations/megabase (mut/Mb)) solid tumors, including NSCLC [ 67 ]. TMB can also be measured in blood-based assays in circulating tumor DNA; however, its clinical utility as a predictive biomarker is still under development [ 68 , 69 ]. In addition to TMB, whole exome sequencing of tumor and matched normal DNA and RNA-seq whole transcriptome analysis, as well as computational bioinformatics, can also be used to predict neoepitopes that can induce an effective anti-tumor immune response, and to develop novel strategies for cancer immunotherapy [ 70 , 71 ].…”
Section: Biomarkers For Potential Use As Predictors Of Neoadjuvant Im...mentioning
confidence: 99%
“…In detail, sub-groups of patients benefitting the most from ICI were good performance status (PS 0-1), reduced number of metastatic sites (0-1) as well as bone or liver involvement ( 17 ). Novel predictive biomarkers are currently being investigated in this context also prospectively, such as for the blood-derived tumor mutational burden ≥16 in the B-F1RST clinical trial (NCT02848651) ( 18 ).…”
Section: Introductionmentioning
confidence: 99%